Effect of addition of clopidogrel to aspirin on stroke incidence: Meta‐analysis of randomized trials. Issue 5 (22nd May 2013) - Palacio, Santiago; Hart, Robert G.; Pearce, Lesly A.; Anderson, David C.; Sharma, Mukul; Birnbaum, Lee A.; Benavente, Oscar R.
<x xml:space="preserve">Abstract</x> Background It remains controversial whether dual antiplatelet therapy reduces stroke more than aspirin alone. Aim We aimed to assess the effects of adding clopidogrel to aspirin on the occurrence of stroke and major haemorrhage in patients with vascular disease. Methods Meta‐analysis of published randomized trials comparing the combination of clopidogrel and aspirin vs. aspirin alone that reported stroke and major bleeding. Results Thirteen randomized trials were included with a total of 90 433 participants (mean age 63 years; 63% male) with a mean follow‐up of 1·0 years and 2011 strokes. Stroke was reduced 19% by dual antiplatelet therapy (odds ratio = 0·81, 95% confidence interval 0·74–0·89) with no evidence of heterogeneity of effect across different trial populations (I2 index = 5%, P = 0·4 for heterogeneity). Dual antiplatelet therapy reduced ischemic stroke by 23% (odds ratio = 0·77; 95% confidence interval 0·70–0·85); there was a nonsignificant 12% increase in intracerebral haemorrhage (odds ratio = 1·12, 95% confidence interval 0·86–1·46). Among 1930 participants with recent (<30 days) brain ischemia from four trials, stroke was reduced by 33% (odds ratio = 0·67, 95% confidence interval 0·46–0·97) by dual antiplatelet therapy vs. aspirin alone. The risk of major bleeding was increased by 40% (odds ratio = 1·40, 95% confidence interval 1·26–1·55) by dual antiplatelet therapy. Conclusions This meta‐analysis demonstrates a substantial relative risk reduction in stroke by clopidogrel plus aspirin vs. aspirin alone that is consistent across different trial cohorts. Major haemorrhage is increased by dual antiplatelet therapy.